Shengxue Busui Decoction activates the PI3K/Akt and VEGF pathways, enhancing vascular function and inhibiting osteocyte apoptosis to combat steroid-induced femoral head necrosis - Manting Liu; Jiexiang Ye; Runtian Wu; Dongqiang Luo; Tao Huang; Dandan Dai; Kexin Wang; Yanping Du; Junwen Ou (Frontiers in Pharmacology)
IntroductionSteroid-induced osteonecrosis of the femoral head (SONFH) is a debilitating condition with no specific treatment. Inhibiting osteocyte apoptosis may be a promising therapeutic approach. Shengxue Busui Decoction (SBD) has shown protective effects against SONFH, but its mechanisms are not fully understood. This study aims to investigate the effects of SBD on SONFH in rats, identifying its key active components and regulatory mechanisms using network pharmacology, bioinformatics, machine learning, and experimental validation.MethodsKey active components and disease targets of SBD were identified through network pharmacology and bioinformatics. GO/KEGG enrichment and ssGSEA analyses were performed to identify critical pathways. Cytoscape and machine learning (SVM) were used for target prediction and molecular docking validation. A dexamethasone (Dex)-induced SONFH rat model was established, and SBD was administered for 60 days. Histological changes were assessed via HE staining, osteoclast activity through TRAP staining, apoptosis levels with TUNEL assays, and vascular function through hematological tests. ELISA was used to measure ALP and OCN levels. In vitro, Dex-induced osteoblast apoptosis in MC3T3-E1 cells was examined to assess SBD’s effect on osteoblast proliferation, apoptosis, and signaling. Western blotting analyzed Caspase-9, Caspase-3, Bax, Bcl-2, and pathway-related proteins. ALP and Alizarin Red staining evaluated osteoblast differentiation and mineralization.ResultsNetwork pharmacology identified curcumin, berberine, and diosgenin as key active components of SBD, with the PI3K/Akt and VEGFR pathways as critical targets, and RAF1, FOXO3, and BRAF as hub genes. In vivo, SBD intervention significantly reduced bone structural damage and apoptosis, decreasing the rate of empty bone lacunae. SBD also increased osteogenic markers ALP and OCN in SONFH rats. In vitro, SBD inhibited osteoblast apoptosis, promoted PI3K/Akt and VEGF pathway expression, and enhanced osteoblast differentiation and mineralization.ConclusionThis study integrates network pharmacology with experimental validation, showing that SBD protects against SONFH by inhibiting osteoblast apoptosis via PI3K/Akt and VEGFR pathways. SBD promotes osteoblast differentiation and mineralization, improving bone structure and vascular function. Curcumin, berberine, and diosgenin are likely key contributors to these effects, highlighting SBD as a potential therapeutic strategy for SONFH.